Laughter in the Adygians’ Pre-Marriage Folklore - L. A. Gutova (Научный диалог)
The article is devoted to the study of the folklore of the pre-marriage period of the life of young people in the traditional Adyghe society. It is noted that, despite the importance of the functions and artistic merit of this stratum of the Adyghe national culture, it has not received wide coverage in the scientific literature, which determines the relevance and novelty of the chosen topic. The analysis involves works whose sphere of existence is public or family celebrations, parties with games and gatherings, other improvised or ritualized actions. It is noted that in the culture of the Adyghe’s there is a long tradition of meeting young men and women before the wedding for a fun pastime, dating, establishing personal relationships, and assigning social roles, which prepared marriage unions. It is shown that at such meetings, young people showed creativity: they participated in games, danced, sang, etc. The role of laughter culture in pre-marriage dialogue is emphasized. Examples of poetic and musical genres of a comic character are given: comic songs, musically intonated verses, and other folklore works that were performed by young people during meetings, for example, nightly gatherings, visits to the sick or wounded, and under other circumstances. It is shown that in the Adyghe pre-marriage folklore the laughter component is multifunctional: it introduces the spirit of freedom into communication, retains ancient magical functions, has a pronounced aesthetic organization.